2021
DOI: 10.3389/fchem.2021.650358
|View full text |Cite
|
Sign up to set email alerts
|

Smart Actuators Based on External Stimulus Response

Abstract: Smart actuators refer to integrated devices that are composed of smart and artificial materials, and can provide actuation and dampening capabilities in response to single/multi external stimuli (such as light, heat, magnetism, electricity, humidity, and chemical reactions). Due to their capability of dynamically sensing and interaction with complex surroundings, smart actuators have attracted increasing attention in different application fields, such as artificial muscles, smart textiles, smart sensors, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…Smart actuators are usually manipulated by a feedback control, communication capabilities, position control, and fault detection, which can be achieved by application of multiple or qualitatively different stimuli (such as light, heat, electricity, magnetism, humidity, pH, etc. ), by programmable logic, and/or by integration of functionally different multiple segments in the same device [16]. For example, a flexible graphene-based Janus film composed of two components, a graphene oxide (GO) layer and a reduced GO (rGO) layer, can roll up on the short-side in response to moisture stimulation due to the hygroscopic expansion of the GO layer, while the film rolls up in the opposite direction under the thermal stimulation, which occurs due to the negative thermal expansion of the rGO layer [17].…”
Section: Trends In Development Of Thermomechanical Energy Convertersmentioning
confidence: 99%
“…Smart actuators are usually manipulated by a feedback control, communication capabilities, position control, and fault detection, which can be achieved by application of multiple or qualitatively different stimuli (such as light, heat, electricity, magnetism, humidity, pH, etc. ), by programmable logic, and/or by integration of functionally different multiple segments in the same device [16]. For example, a flexible graphene-based Janus film composed of two components, a graphene oxide (GO) layer and a reduced GO (rGO) layer, can roll up on the short-side in response to moisture stimulation due to the hygroscopic expansion of the GO layer, while the film rolls up in the opposite direction under the thermal stimulation, which occurs due to the negative thermal expansion of the rGO layer [17].…”
Section: Trends In Development Of Thermomechanical Energy Convertersmentioning
confidence: 99%
“…78 The combination of pH, temperature, redox, and light stimulation induces a change in the structure, size, and chemical or physical properties of multi stimulusresponsive nano-carriers. 79,80 For example, Gao et al synthesized the metal/semiconductor composite material Au NR@CuS. 81 The large octahedral void space could be used to load a large amount of drug methotrexate (MTX) for chemotherapy and modified with vasoactive intestinal peptide (VIP) and hyaluronic acid (HA) to form VIP-HA Au NR@CuS NPs targeting synovial cells in RA.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…A magnetic field can pass through most magnetic materials, and therefore magnetic field-stimulus-responsive materials are widely considered to have the potential to be utilized in some specific space fields due to the competitive responsive performances, self-assembling properties and easy magnetic manipulation. 9 Recently, LCs doped with various types of particles have received huge attention due to the particles' physical properties in combination with LCs' anisotropic and stimuli-responsive properties. [10][11][12] Taking into consideration the advantages of magnetic manipulation, a number of studies on ferromagnetic LCs including ferronematics have been reported that deal with LCs doped with magnetic nanoparticles, which can be manipulated using a very weak external magnetic field.…”
Section: Introductionmentioning
confidence: 99%